Considering river structure and stability in the light of evolution: feedbacks between riparian vegetation and hydrogeomorphology. Issue 2 (18th September 2014) - Corenblit, Dov; Davies, Neil S.; Steiger, Johannes; Gibling, Martin R.; Bornette, Gudrun
Abstract River ecological functioning can be conceptualized according to a four‐dimensional framework, based on the responses of aquatic and riparian communities to hydrogeomorphic constraints along the longitudinal, transverse, vertical and temporal dimensions of rivers. Contemporary riparian vegetation responds to river dynamics at ecological timescales, but riparian vegetation, in one form or another, has existed on Earth since at least the Middle Ordovician (c. 450 Ma) and has been a significant controlling factor on river geomorphology since the Late Silurian (c. 420 Ma). On such evolutionary timescales, plant adaptations to the fluvial environment and the subsequent effects of these adaptations on fluvial sediment and landform dynamics resulted in the emergence, from the Silurian to the Carboniferous, of a variety of contrasted fluvial biogeomorphic types where water flow, morphodynamics and vegetation interacted to different degrees. Here we identify several of these types and describe the consequences for biogeomorphic structure and stability (i.e. resistance and resilience), along the four river dimensions, of feedbacks between riparian plants and hydrogeomorphic processes on contrasting ecological and evolutionary timescales. Copyright © 2014 John Wiley & Sons, Ltd.